Quantum device fine-tuning using unsupervised embedding learning - N M van Esbroeck; D T Lennon; H Moon; V Nguyen; F Vigneau; L C Camenzind; L Yu; D M Zumbühl; G A D Briggs; D Sejdinovic; N Ares (New Journal of Physics, 2020)
Quantum devices with a large number of gate electrodes allow for precise control of device parameters. This capability is hard to fully exploit due to the complex dependence of these parameters on applied gate voltages. We experimentally demonstrate an algorithm capable of fine-tuning several device parameters at once. The algorithm acquires a measurement and assigns it a score using a variational auto-encoder. Gate voltage settings are set to optimize this score in real-time in an unsupervised fashion. We report fine-tuning times of a double quantum dot device within approximately 40 min.